Pengenalan dan Pemanfaatan Potensi Lokal: Pendampingan Pembuatan Brownie X Nangka sebagai Produk Khas Desa Sahang - Andriana Tina Putri Dewi Anggraini; Silachi Agusta Adi Putra (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The problem in Sahang Village is that jackfruit, which is abundant, is only used in traditional ways with low economic value. From this problem, the research formulates two main focuses: how the process of making Brownie x Jackfruit as a local food innovation, and what factors support or hinder its development. The purpose of this research is to know, explore, and describe the potential of jackfruit, the innovation process, and the prospects of the product as a village culinary icon. The study employed the Asset Based Community Development (ABCD) approach through the stages of discovery, dream, design, and define/deliver, with data collected from interviews, participatory observation, focus group discussions (FGD), documentation, and product trials, then analyzed qualitatively using data reduction, presentation, and conclusion drawing. The results show that Brownie x Jackfruit is well received by the community and adds value to local products, but still faces challenges such as limited equipment, packaging, and marketing strategies. Even so, the product has strong potential to support the local economy, empower the community, and strengthen the cultural identity of Sahang Village.